OC-055 A prospective study validating a novel and simple polyp classification and comparing the outcomes between a Japanese expert and Western expert in a UK setting. (23rd September 2015) - Longcroft-Wheaton, G R; Mead, R; Uraoka, T; Bhandari, P
Abstract : Introduction: Small hyperplastic Polyps have a very low malignant potential. However, they are currently being removed due to the lack of in-vivo histology techniques. Japanese endoscopists have published excellent results based on Kudo's pit pattern. However, most of the published literature has used zoom endoscopy and vital stains, such as cresyl violet, and Kudo's classification is difficult and inpractical to apply in a UK setting. Prospective validation of a new and easy mucosal pattern classification (NAC) Prospective comparison of the diagnostic accuracy of NAC classification when assessing colonic polyp using non-zoom endoscopes and indigo carmine dye spray. Methods: NAC classification is based on three features: Mucosal patterns, vascular patterns and vascularity. Based on this polyps can be graded as N (non-neoplastic) A (adenoma) C (cancer). Fujinon non-zoom EC-590 colonoscopes with the EPX 4400 processor was used. Polyps were prospectively and independently assessed by a Japanese and a UK expert during screening colonoscopy, before and after indigo carmine dye spray. The lesions were subsequently removed to obtain the true diagnosis. MathCAD was used to process the statistics and chi2 test performed. Results: A total of 121 polyps were evaluated. 60 polyp pictures from a prospective library for the validation exercise, and 61 polyps were prospectively examined during colonoscopy. Polyps evaluated during live endoscopy (61) showed the median polyp size was 7 mm (range 3–40 mm) (see Abstract 055 ). A chi2 test did not show any significant difference between the Japanese (Limb J) and UK (limb U) results (p=0.8). Sensitivity was 91% (J) and 87% (U). Specificity was 93% for J and U. Diagnostic accuracy was 92% (J) and 89% (U).